Sexual Harassment in Clinical Practice—A Cross-Sectional Study Among Nurses and Nursing Students in Sub-Saharan Africa. (October 2020) - Tollstern Landin, Teresia; Melin, Tove; Mark Kimaka, Victoria; Hallberg, David; Kidayi, Paulo; Machange, Rogathe; Mattsson, Janet; Björling, Gunilla
Introduction: Sexual harassment (SH) at the workplace is a globally discussed topic and one deserving of scrutiny. It is an issue that is often avoided although around 25% of nurses worldwide have experienced some form of SH at their workplace. Consequences of SH at workplaces can be very serious and an occupation hazard for nurses around the world. In Sub-Saharan Africa there is also a need for more studies in the field. Objective: The overall aim was to determine the prevalence, types, and consequences of sexual harassment among nurses and nursing students at a regional university hospital in Tanzania. Methods: The study has a cross-sectional design. A study specific questionnaire was distributed to a total of 200 nurses and nursing students. Descriptive statistics were used for calculation of frequencies, prevalence, including gender differences, types, and consequences of sexual harassment. Results: The result show that 9.6% of the participants had experienced some form of SH at their workplace. Regarding the female nurses and students, 10.5% had been sexually harassed at work, whereas the number for males was 7.8%, but 36% knew about a friend who had been sexually harassed. The most common perpetrator were physicians. The victims of SH were uncomfortable going back to work, felt ashamed and angry. Conclusions: In conclusion, nearly 10% of the participants had been exposed to sexual harassment. However, an even greater number of victims was found when including by proxy victims of sexual harassment. SH can become a serious occupational hazard and stigmatization for nurses. Enhanced knowledge is needed, and hospitals and medical colleges should emphasize their possibilities to give support and assistance to the victims of SH. Education about SH in all levels and prevention methods should also be emphasized.